The relative age in handball players in Portugal - Paulo Sá; Rui Resende; A. Rui Gomes; Miguel Saavedra; Juan J. Fernández (Federación Extremeña de Balonmano; University of Extremadura, 2020)
Relative age effect is a subject that has been studied as a differentiating factor between athletes' development. This study aimed to determine whether handball players have more possibilities to get to high performance, according to the month and year of birth and to verify this chance accordingly to their sex. Were selected 13630 handball players representing the totality of handball players of Portugal. Variables related to sex, competition, internationalizations and date of birth of all players were analyzed. It was verified if the year of birth was even or odd and the variable trimester of birth. To determine the relative age effect, chi-square was used. To assess the lead of birth in even year, the differences in the proportion of births in even and odd years were verified by binomial test. A statistically significant effect of relative age was found. This effect was not found in First League, but rather in formation groups. The relative age effect is observed in both players selected for the national teams in lower categories and among the non-international players and did not occur in the international ones. In general, there was also not found any trend for more players to be born in even years than in odd years. Keywords: talent selection; birth year; age sport groups.